2016
DOI: 10.1016/j.dib.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the amyloid pore forming properties of rat and human Alzheimer’s beta-amyloid peptide 1-42: Calcium imaging data

Abstract: The data here consists of calcium imaging of human neuroblastoma SH-SY5Y cells treated with the calcium-sensitive dye Fluo-4AM and then incubated with nanomolar concentrations of either human or rat Alzheimer’s β-amyloid peptide Aβ1-42. These data are both of a qualitative (fluorescence micrographs) and semi-quantitative nature (estimation of intracellular calcium concentrations of cells probed by Aβ1-42 peptides vs. control untreated cells). Since rat Aβ1-42 differs from its human counterpart at only three am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…To test the therapeutic potential of AmyP53, we developed a sensitive amyloid pore assay based on the detection of Ca 2+ fluxes induced by amyloid pore oligomers generated in the minutes following the addition of nanomolar concentrations of Aβ1-42 or α-syn to recipient SH-SY5Y cells [32,33]. Using this assay, we demonstrated that AmyP53 prevents the formation of such amyloid pores (both wild type Aβ and α-syn, but also mutated forms including A30P, E46K and A53T that are associated with inherited forms of PD) [32].…”
Section: Introductionmentioning
confidence: 99%
“…To test the therapeutic potential of AmyP53, we developed a sensitive amyloid pore assay based on the detection of Ca 2+ fluxes induced by amyloid pore oligomers generated in the minutes following the addition of nanomolar concentrations of Aβ1-42 or α-syn to recipient SH-SY5Y cells [32,33]. Using this assay, we demonstrated that AmyP53 prevents the formation of such amyloid pores (both wild type Aβ and α-syn, but also mutated forms including A30P, E46K and A53T that are associated with inherited forms of PD) [32].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms of Aβ neurotoxicity is complex and not fully understood. Aβ can damage neurons through dysregulation of cellular ionic homeostasis by two main routes: (i) modulation of certain ion channels in plasma or intracellular membranes 18 , 19 or (ii) permeabilization of cell membranes through direct membrane insertion and ion channel formation 7 , 20 33 . Aβ 1-42 and Aβ 1-40 induced ion conductance in lipid membranes 20 , 27 , 34 .…”
Section: Introductionmentioning
confidence: 99%
“…of cellular ionic homeostasis by two main routes: (i) modulation of certain ion channels in plasma or intracellular membranes 18,19 or (ii) permeabilization of cell membranes through direct membrane insertion and ion channel formation 7,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] . Aβ 1-42 and Aβ 1-40 induced ion conductance in lipid membranes 20,27,34 .…”
mentioning
confidence: 99%
“…The mechanism of toxicity involves the penetration of small oligomers into the membrane and formation of unregulated ion channels, which lead to ion leakage and, ultimately, cell death [11][12][13][14][15]. Scala et al found that calcium could pretreat through the pore formed by beta-amyloid peptide [16]. However, the hypothesis of an ionic channel formed from Aβ peptides is still under the debated.…”
Section: Introductionmentioning
confidence: 99%